Proteolytic activity in cowshed dust extracts induces C5a release in murine bronchoalveolar lavage fluids which may account for its protective properties in allergic airway inflammation. Issue 1 (23rd October 2012) - Stiehm, Matthias; Bufe, Albrecht; Peters, Marcus
Abstract : Objective: Intranasal application of cowshed dust extract (CDE) during sensitisation in a murine model of experimental asthma leads to a significant alleviation of the clinical parameters of the allergic immune response. However, neither the immunological mechanisms underlying this protective effect nor all of the protective substances included in CDE have yet been described. Recently, complement factor 5a (C5a) receptor signalling has been identified to play a regulatory role in allergic airway disease. Thus we investigated whether CDE can activate the complement system to release biologically active C5a in the lung. Methods: Proteins included in CDE were identified by mass spectrometry. Complement cleaving activity of a serine protease identified in CDE was validated with the purified enzyme, and the biological activity of the released C5a was determined. C5a was applied in a murine model of allergy to prove its protective impact on allergic airway disease. Results: CDE induced the release of C5a in murine bronchoalveolar lavages (BAL). We identified a serine protease from the midgut of tenebrio molitor larvae in CDEs which was able to induce the release of biologically active C5a in murine BAL. We applied C5a in different doses to female Balb/c mice during the sensitisation phase and during the first antigen challenge and showed that C5a has the ability to dampen important parameters of allergic airway inflammation, such as infiltration of proinflammatory cells into lung tissue or Th2 cytokine secretion by lung cells. Conclusions: We conclude that the C5a generating enzyme included in CDE might account for some of the allergy protective effects of CDE by generation of C5a in murine lungs.